Co‐targeting androgen receptor and DNA for imaging and molecular radiotherapy of prostate cancer: In vitro studies. Issue 16 (11th September 2014) - Han, Guang; Kortylewicz, Zbigniew P.; Enke, Thomas; Baranowska‐Kortylewicz, Janina
<x xml:space="preserve">Abstract</x> BACKGROUND The androgen receptor (AR) axis, the key growth and survival pathway in prostate cancer, remains a prime target for drug development. 5‐Radioiodo‐3′‐O‐(17β‐succinyl‐5α‐androstan‐3‐one)‐2′‐deoxyuridin‐5′‐yl phosphate (RISAD‐P) is the AR‐seeking reagent developed for noninvasive assessment of AR and proliferative status, and for molecular radiotherapy of prostate cancer with Auger electron‐emitting radionuclides. METHODS RISAD‐P radiolabeled with 123I, 124I, and 125I were synthesized using a common stannylated precursor. The cellular uptake, subcellular distribution, and radiotoxicity of 123I‐, 124I‐, and 125IRISAD‐P were measured in LNCaP, DU145, and PC‐3 cell lines expressing various levels of AR. RESULTS The uptake of RISAD‐P by prostate cancer cells is proportional to AR levels and independent of the radionuclide. The intracellular accumulation of radioactivity is directly proportional to the extracellular concentration of RISAD‐P and the duration of exposure. Initially, RISAD‐P is trapped in the cytoplasm. Within 24 hr, radioactivity is associated exclusively with DNA. The RISAD‐P radiotoxicity is determined by the radionuclide; however, the cellular responses are directly proportional to the AR expression levels. LNCaP cells expressing high levels of AR are killed at the rate of up to 60% per day after a brief 1 hr RISAD‐P treatment. For the first time, the AR expression in PC‐3 and DU 145 cells, generally reported as AR‐negative, was quantitated by the ultra sensitive RISAD‐P‐based method. CONCLUSIONS RISAD‐P is a theranostic drug, which targets AR. Its subcellular metabolite participates in DNA synthesis. RISAD‐P is a promising candidate for imaging of the AR expression and tumor proliferation as well as molecular radiotherapy of prostate cancer. Prostate 74: 1634–1646, 2014. © 2014 Wiley Periodicals, Inc.